2016
DOI: 10.1021/acs.biochem.6b00731
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Desolvation and Thermostability Trade-Offs in the Evolution of Catalytically Diverse Triazine Hydrolases

Abstract: The desolvation of ionizable residues in the active sites of enzymes and the subsequent effects on catalysis and thermostability have been studied in model systems, yet little about how enzymes can naturally evolve to include active sites with highly reactive and desolvated charges is known. Variants of triazine hydrolase (TrzN) with significant differences in their active sites have been isolated from different bacterial strains: TrzN from Nocardioides sp. strain MTD22 contains a catalytic glutamate residue (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 95 publications
(178 reference statements)
1
11
0
Order By: Relevance
“…The lack of a loop next to the UFC1 active site makes the latter heavily solvated by the electrophilic protons supplied by the water. This causes the active site Cys to be less potent for the nucleophilic attack, and thereby requires desolvation prior to its nucleophilic attack [33][34][35][36] . This motivated us to investigate whether UBA5 residues 347-377 play a role in UFC1 active site desolvation.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of a loop next to the UFC1 active site makes the latter heavily solvated by the electrophilic protons supplied by the water. This causes the active site Cys to be less potent for the nucleophilic attack, and thereby requires desolvation prior to its nucleophilic attack [33][34][35][36] . This motivated us to investigate whether UBA5 residues 347-377 play a role in UFC1 active site desolvation.…”
Section: Resultsmentioning
confidence: 99%
“…Although dynamics have been invoked to explain the catalytic power of some enzymes 56575859 , the physical basis for how these motions are related to catalysis remains controversial 60 . Nevertheless, experimental work has suggested that evolution of effective enzymes requires a balance of stability and flexibility to effectively tune function 61 for specific environmental niches 62 . The results of this study suggest that conformational heterogeneity or flexibility can be used as a mechanism for tuning electrostatic energies for their functional roles.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that conformational heterogeneity or flexibility can be used as a mechanism for tuning electrostatic energies for their functional roles. Although the timescales of motions in this study are too slow to be relevant to catalysis, the relationship between flexibility 6361 and stability 62 , and the propensity of proteins to sample alternative states in response to charge burial, must be accounted for in the de novo design of novel enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of the desolvated general acid Glu173 into the binding pocket of an ancestral SBP, despite initially being an adaptation for a different function, may have been sufficient for initial, promiscuous CDT activity. Indeed, the intrinsic reactivity of desolvated acidic and basic residues has been exploited similarly in enzymes that have evolved recently in response to anthropogenic substrates 20 and in enzymes engineered via single substitutions in non-catalytic proteins 21 . Following the introduction of a reactive general acid, optimization of enzyme-substrate complementarity and the introduction of hydrogen-bonding networks to position the catalytic residue precisely and stabilize the departing carboxylate group of the substrate appear to have occurred.…”
Section: Main Textmentioning
confidence: 99%